Immediate inguinal lymphaticovenous anastomosis following lymphadenectomy in skin cancer of lower extremities - Wanchalerm Chungsiriwattana (2022)
Background: Secondary lymphedema following inguinal lymph node dissection in lower extremities skin cancer reduce the patients’ quality of life. Immediate lymphaticovenous anastomosis (LVA) at groin is a procedure intended to prevent secondary lymphedema. The data regarding the long-term efficacy and safety of this procedure was limited. Therefore, we evaluated the long-term outcomes of immediate LVA in patients with melanoma and non-melanoma skin cancer of the lower extremities. Methods: The retrospective data review of patients with melanoma or squamous cell carcinoma of the lower extremities underwent oncologic tumor resection with groin node dissection between December 2013 and December 2016 was performed. Seven patients underwent immediate LVA (intervention) at groin after node dissection and 22 acted as controls. The occurrence of lymphedema and oncologic outcomes were followed up to 7 years. Results: Fifteen patients (51.7%) developed postoperative lymphedema, which were three patients in the intervention group and twelve patients in the control group (p = 0.68). The intervention group had significant lower 2-year (57.1% versus 77.3%) and 5-year overall survival (14.3% versus 54.5%) (p = 0.035). The intervention group had reduced 2-year (28.6% versus 86.4%) and 5-year (28.6% versus 68.2%) Recurrence Free Survival (RFS) (p = 0.013). The intervention group also had reduced 2-year (0% versus 90%) and 5-year (0% versus 70%) Metastasis Free Survival (MFS) (p = 0.003). Conclusion: Immediate inguinal LVA following groin node dissection in lower extremity skin cancer patients did not reduce the incidence of lymphedema. Unfortunately, it was associated with lower overall survival and an increase in tumor recurrence and metastasis.